Observation of spin dependent electrochemical potentials at room temperature in a quantum well structure - Park, Youn Ho; Kim, Hyun-jun; Chang, Joonyeon; Koo, Hyun Cheol (ELSEVIER SCIENCE BV, 2017)
Spin transport with a strong Rashba spin splitting is observed in a semiconductor channel. Using the current injection into the side of the quantum well, the potentiometric signal and the spin-torque-induced magnetization change are simultaneously detected. In this geometry, the spin current is directly injected from the ferromagnetic electrode into the quantum well channel and the electro-chemical potential is monitored by the detection ferromagnet. For the side injection instead of vertical injection, the milling of the top cladding layer is not necessary, so the efficient spin transport and the undamaged Rashba spin splitting can be realized. The ferromagnetic detector senses the Rashba-effect-induced electrochemical potential shift brought by the charge current and this potentiometric signal is also modified by the magnetization rotation induced by the spin current. The large potential changes of 1.03 Omega and 0.96 Omega are observed at 1.8 K and 300 K, respectively. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ELECTRICAL DETECTION; INJECTION; PRECESSION